ANALYSIS OF INTEGRATED AGRICULTURE FARMING PROGRAM (SIMANTRI) IN MENDOYO DAGIN TUKAD VILLAGE, JEMBRANA, BALI, INDONESIA - IGA.Angga Prasetya Budiarta; Sujarwo Sujarwo (Agricultural Socio-Economics Journal, 2016)
The objectives of this study are to analyze the implementation of the Simantri program in Mendoyo Dangin Tukad Village and to analyze the profit level of the Simantri farmers and non-Simantri farmers. The analyses used are descriptive statistics and profits analysis. This study began in the first planting season, which is Januari-April 2016. The sample total is 40 farmers, which consist of 20 farmers joining Simantri program and 20 farmers are not. The non-Simantri farmers are chosen purposively considering similarity among those who join in the Simantri program. The result shows that the implementation of the program in Mendoyo Dangin Tukad runs well. The waste processing of livestock in the village has benefit in reducing external input needs, such as inorganic fertilizer and pesticides. Waste of plants and animals are useful material for raising livestock, increasing land fertility and producing bio-energy. The farmers’ profit earned Simantri program is greater than the farmers who do not participate in the program. The source of the increasing farming profit is coming from reducing external inputs of fertilizer and pesticides used.